2006
DOI: 10.1243/09544054jem586
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and processing the acoustic emission signals from the friction-stir-welding process

Abstract: This paper discusses the detection and analysis of the acoustic emission (AE) signals to investigate the possibility of applying the AE technique for the in-process monitoring of the friction-stir-welding process. Tests are carried out for joining similar and dissimilar metals using a high-speed rotating tool under various rotational speeds and traverse speeds and for different tool penetration depths. The results of fast Fourier transform show that the amplitude of the AE signal in the frequency domain is sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…11 Therefore, other signal processing techniques are utilised to characterise the AE signal over these frequency ranges. The wavelet transformation has been utilised in this work to obtain a series of decomposed vibroacoustical signals.…”
Section: Frequency Analysismentioning
confidence: 99%
“…11 Therefore, other signal processing techniques are utilised to characterise the AE signal over these frequency ranges. The wavelet transformation has been utilised in this work to obtain a series of decomposed vibroacoustical signals.…”
Section: Frequency Analysismentioning
confidence: 99%
“…They showed the presence of sudden changes in signal but those changes can also correspond to some other stresses as well as they have not shown the exact location of defects. Soundararajan et al [19] showed that acoustic emissions produced are time variant only during plunge phase but is steady during welding. They have applied FFT, STFT, and wavelet transforms on signals but found difficult to correlate the frequency of the signal directly to various interactions that occur during the process.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by a more precise representation of the behaviour of the phenomenon, but its high complexity must be considered in the analysis. Different works reported [7][8][9][10][11] show the application of nondestructive techniques (NDT) on the mechanical and manufacturing processes.…”
Section: Introductionmentioning
confidence: 99%
“…Soundararajan et al [7] determined the correlation between the losses of contact of the tool with the workpiece based on features of the AE signal, using the Fast Fourier Transform (FFT), the Short-Time Fourier Transform (STFT), and the Discrete Wavelet Transform (DWT). The authors investigated the possibility of applying AE techniques for the in-process monitoring of the FSW process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation